数学 过程 计算 正确

来源:百度知道 编辑:UC知道 时间:2024/07/06 13:42:50
49.7-[-23/3/4+(18.7-25.25)]
12+1又3/4-8又5/12-6.75
-(-3)^2-(1又1/2)*2/9-6/|-1/3|^3
-2^5/(-4)*(1/2)^2-1/12*(-5*2^3)^2
1又2/3-5又3/4-2^3/[(1/2)^2+3*(-3/4)]*1/8
(-0.1)^3-1/4*(-3/5)^2
(-2又3/4)/1又1/8-(-6)*(2/3-(-2)^3
-3^2*(-4/27)+(-3)^3/2又1/4*(-2/3)^2+4
[2又1/2-(3/8+1/6-3/4)*24]/(-3^2+4)*(-1)^2009
-32又16/25/(-8*4)-(1/2+2/3-3/4-11/12)*(-24)
-4.165*4/7+7.665*4/7-(7/18-5/6+7/9)/(-1/6)

第1题的题目中(-23/3/4)有两种理解,
一是(-23)/(3/4),另一是(-23/3)/4,分别运算如下:
49.7-[-23/3/4+(18.7-25.25)]
=49.7-(18.7-25.25-23*4/3)
=(49.7-18.7)+(25.25+23*4/3)
=31+(25+1/4)+(30+2/3)
=(31+25+30)+(1/4+2/3)
=86+11/12

49.7-[(-23/3)/4+(18.7-25.25)]
=49.7+(23/3)/4-18.7+25.25
=(49.7-18.7)+(25.25+23/3*4)
=31+(25+3/12+23/12)
=56+26/12
=58+1/6

2.
12+1又3/4-8又5/12-6.75
=12+1+3/4-8-5/12-6-3/4
=(12+1-8-6)+(3/4-5/12-3/4)
=-1-5/12
=-(1+5/12) 或=-17/12

3.
-(-3)^2-(1又1/2)*2/9-6/|-1/3|^3
=-9-(3/2)*2/9-6*27
=-9-1/3-162
=-(171+1/3) (即-171又1/3)

4.
-2^5/(-4)*(1/2)^2-1/12*(-5*2^3)^2
=2-1/12*40^2
=2-(20^2)/3
=2-133-1/3
=-(131+1/3)

5.
1又2/3-5又3/4-2^3/[(1/2)^2+3*(-3/4)]*1/8
=(1+2/3)-(5+3/4)-8/[1/4-9/4)]*1/8
=(1+2/3)-(5+3/4)-8/(-2)*1/8
=(1-5)+(2/3-3/4)+1/2
=-4+(8-9+6)/12
=-4+5/12

6.
(-0.1)^3-1/4*(-3/